Analytical Solution for Consolidation Behaviors of Combined Composite Foundation Reinforced with Penetrated PCCSs and Floating DM Columns. (18th February 2023) - Zhang, Chaozhe; Zhang, Dingwen; Liu, Songyu; Han, Jianyong; Jiang, Chen; Zhao, Yue
Abstract : As the composite pile, the precast concrete piles reinforced with cement-treated soil (PCCS) is formed by driving the precast cement (PC) pile into the deep mixing (DM) column, which has been successfully and widely utilized to support buildings and embankments over soft soil. To increase the pile spacing and give full play to the economic merits of the PCCS, a reinforcement scheme, which involves the combined use of rigid piles and flexible columns, employing penetrated PCCSs and floating DM columns is proposed and utilized for soft soil ground treatment. However, there is a lack of feasible method for consolidation behaviors of this combined composite foundation (CCF) reinforced with penetrated PCCSs and floating DM columns under flexible loads. This paper developed an analytical solution to predict the average consolidation degree of this CCF based on a cylinder consolidation model and double-layer ground consolidation theory. The excess pore pressure and average consolidation degree were calculated by considering the composite pile penetration into the cushion. The analytical method agrees well with results obtained by numerical analysis. Additionally, a parametric study was conducted systematically to analyze the effect of key influence factors on the average consolidation degree of this CCF. The results indicate that the consolidation rate of this CCF can be much faster than that of the natural ground. The consolidation rate strongly depends on the compressive modulus and area replacement ratio of PCCSs. The increasing inner core-outer core modulus ratio and the inner core-subsoil modulus ratio increase the consolidation rate of this CCF. In addition, the consolidation rate increases with the gravel cushion-subsoil modulus ratio, while it decreases with the loading period.